The Law Issues Zakat With The Value Of Silver Nisab When There Is A Large Difference In Value Between Gold And Silver Nisab - Mananu, Rizal; Bakri, Mukhlis; Rahmat, Fajar; Hijaz, Chiar; Yusuf, Andi Asdar (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2023)
The determination of nisab zakat is an important discussion in Islam, especially in the context of the vast difference in value between nisab gold and silver. Three opinions arise in determining the nisab zakat when there is a large difference in value between the gold and silver nisab, namely obligatory with gold nisab, obligatory with silver nisab, and using the lowest nisab of the two. This study aims to analyze these three opinions using analytical descriptive methods. Data are obtained from Islamic literature and compiled to understand the legal basis as well as the social and religious implications of each opinion. The analysis shows that all three opinions have a strong legal basis, but using the value of silver nisab as the nisab with the lowest value as the standard nisab zakat of treasure is more appropriate in the context of the difference in value between gold and silver nisab. Thus, the conclusion of this study is that the use of silver nisab value is a more appropriate approach in determining zakat obligations because it is safer for muzakki and more beneficial for the poor.